Maternal Factors and Neonatal Mortality and Morbidity Associated with Late Preterm Birth - Heidi K. Al-Wassia (Journal of King Abdulaziz University: Medical Sciences, 2023)
The objective of this study is to ascertain risk factors and outcomes associated with late preterm birth. A 1:1 matched case-control study of mothers who delivered at 34+0 to 36+6 weeks gestation (cases) and at term (controls) at King Abdulaziz University Hospital, Jeddah, Saudi Arabia between June 1st, 2014 and March 30th, 2015. We enrolled 53 cases and 53 controls. Mothers of late preterm infants were older (p = 0.03), with higher parity (p = 0.04), body mass index (p = 0.01) and multiple pregnancies (p = < 0.001) compared to mothers of infants born at term. A higher proportion of hypertension and (p = 0.01) and premature rupture of membrane (p = < 0.001) preceded late preterm deliveries. Cesarean section frequency was greater in late preterm infants (p = 0.002). Late preterm infants were admitted to the neonatal intensive care unit more frequently than their term counterparts (p = < 0.001), had more respiratory adverse outcomes (p = 0.006) and longer hospital stay (p = 0.001). Late preterm birth is a substantial perinatal health problem warranting a closer look at eff orts to improve prenatal care strategies to reduce risk factors associated with it and prevent non-medically indicated premature birth.